Benchmarks for multicomponent reactive transport across a cement/clay interface - Marty, Nicolas C. M.; Bildstein, Olivier; Blanc, Philippe; Claret, Francis; Cochepin, Benoit; Gaucher, Eric C.; Jacques, Diederik; Lartigue, Jean-Eric; Liu, Sanheng; Mayer, K. Ulrich; Meeussen, Johannes C. L.; Munier, Isabelle; et al. (Computational geosciences, 2015)
The use of the subsurface for CO 2 storage, geothermal energy generation, and nuclear waste disposal will greatly increase the interaction between clay(stone) and concrete. The development of models describing the mineralogical transformations at this interface is complicated, because contrasting geochemical conditions (Eh, pH, solution composition, etc.) induce steep concentration gradients and a high mineral reactivity. Due to the complexity of the problem, analytical solutions are not available to verify code accuracy, rendering code intercomparisons as the most efficient method for assessing code capabilities and for building confidence in the used model. A benchmark problem was established for tackling this issue. We summarize three scenarios with increasing geochemical complexity in this paper. The processes considered in the simulations are diffusion-controlled transport in saturated media under isothermal conditions, cation exchange reactions, and both local equilibrium and kinetically controlled mineral dissolution-precipitation reactions. No update of the pore diffusion coefficient as a function of porosity changes was considered. Seven international teams participated in this benchmarking exercise. The reactive transport codes used (TOUGHREACT, PHREEQC, with two different ways of handling transport, CRUNCH, HYTEC, ORCHESTRA, MIN3P-THCm) gave very similar patterns in terms of predicted solute concentrations and mineral distributions. Some differences linked to the considered activity models were observed, but they do not bias the general system evolution. The benchmarking exercise thus demonstrates that a reactive transport modelling specification for long-term performance assessment can be consistently addressed by multiple simulators.